Teleology and oracular prophecies: narratological analysis of cultic etiologies in book VII of Herodotus’ ‘Histories’ - Fernandes Moreira, Matheus (Romanitas - Revista de Estudos Grecolatinos, 2023)
This article aims to investigate how the oracular propheciesthat led to the inauguration of Greek cultic practices integrates the teleological structure of Herodotus’ work. With an emphasis on book VII of the Histories, the investigation will approach the impact of predictions on the narrative dimensions of the work. Bounding the main plot to cultic etiological digressions, the predictions compose the historian’s argumentative web enunciating justifications related to Greek religious precepts. By searching different dimensions of the past, the oracular lens employed in the historian’s retrospective performance rescues mythological, literary traditions and ritual practices. These partake in his effort to give meaning to the past and, simultaneously, highlight its pertinence considering the context in which the work was published.
Keywords: Historiography; Teleology; Etiology; Prophecy; Cult